LH level on the antagonist administration day as a predictor of the reproductive outcomes in women with normal ovarian function - Pang, Conghui; Wang, Kehua; Wang, Ruihan; Guo, Danyang; Wen, Zixi (Frontiers in Endocrinology, 2023)
Introduction:The addition of antagonists is mainly based on estrogen level and follicle size, while LH level has not received sufficient attention.In this study, LH Level on the antagonist administration day was used as the main research objective to explore its relationship with laboratory indicators and pregnancy outcomes. Methods and Analysis:We enrolled 854 patients with normal ovarian function undergoing in-vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) between May 2021 to May 2022 at the Reproductive Center of Shandong University of Traditional Chinese Medicine.We used the quartile method to group LH levels on the antagonist administration day. There were four groups: Q1 (0.53IU/L≤LH≤1.89IU/L); Q2 (1.89IU/L